PENGARUH LIKUIDITAS, PROFITABILITAS, LEVERAGE DAN UMUR PERUSAHAAN TERHADAP AUDIT DELAY: (STUDI KASUS PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI TAHUN 2017-2020) - Cita Ayu Suminar; Zulkifli Zulkifli; Manendha Maganitri Kundala (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The study aims to analyze the effect of liquidity, profitability, leverage and company age on audit delay in LQ-45 companies listed on the IDX in 2017-2020. The sampling method used was purposive sampling and obtained a sample of 22 companies. The research method use quantitative methods by doing multiple linier regression between the variable liquidity, profitability, leverage and company age on audit delay. his study concludes that profitability variable had an effect on audit delay in LQ-45 companies listed on the IDX in 2017-2020. While liquidity, leverage and company age have no effect on audit delay in LQ-45 companies listed on the IDX in 2017-2020. Smimultaneously iqudity, profitability, leverage and company age had an effect on audit delay in LQ-45 companies listed on the IDX in 2017-2020.